Socio demographic profile of GDM using 75 gm OGCT - P., Muthuprabha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The aim of this study was to study the prevalence of GDM in a tertiary care centre based on 75 gm OGCT and to analyse the socio demographic and clinical profile of GDM using 75 gm OGCT in a tertiary care centre. Methods: This study was conducted in the antenatal OPD of Tirunelveli Medical College Hospital from October 2014 to July 2015, a period of 10 months on 300 antenatal women. The mothers were screened using 75gm 2-hour OGCT once during each trimester and the results analysed. Results: The prevalence of GDM in this study was 3.4%. Out of this 47-50% of women with GDM were of the age group 26-30 years. 6% of the women had BMI of >25 kg/m2. The incidence of GDM was found to be high in multigravidas and 70% belonged to class V socioeconomic status. Using the 75 gm OGTT 20%, 40% and 40% were diagnosed during the I, II and III trimesters respectively. 90% of the women delivered at term and total caesarean section rate was 30.6%. Mean birth weight of the babies was 2.9 kg. 70% of the diagnosed GDM women were treated using Medical Nutrition Therapy (MNT). Conclusions: 75gm OGCT recommended by WHO can be used to detect significant number of cases of GDM.